TINJAUAN YURIDIS KEDUDUKAN PEREMPUAN SEBAGAI AHLI WARIS MENURUT HUKUM WARIS MASYARAKAT ADAT KARO - Olo Chris Simadi Pandia; Rayani Saragih; Maslon Hutabalian (Journal Recht (JR), 2022)
This study discusses the juridical review of the position of women as heirs according to the inheritance law of the Karo adat community. The purpose of this study is to determine the position of women in the Karo indigenous peoples, to know the mechanism of inheritance distribution in the Karo people and to find out what factors influence the development of women's inheritance rights in the Karo customary inheritance law. This research method uses descriptive analytical method, is descriptive because this study aims to carefully describe the characteristics of the facts (individuals, groups or circumstances), and to determine the frequency of something that happens while the data analysis used in this study is qualitative data analysis. , is data that is not in the form of numbers but is based on statutory regulations, jurisprudence, the views of resource persons so that it can answer the problems of this research. The results of this study indicate that the position of women in Karo adat as children before marriage will still be included in their father's group, but that position will change after she gets married, because women will follow her husband's clan or family. After becoming a wife, her position follows her husband's clan or family, a wife whose husband dies is different from a divorce but is still considered part of her husband's family. On the other hand, if there is a divorce, the widow returns to her original family. Her relationship with her husband is traditionally cut off and daughters in the Karo community are not the heirs according to the patrilineal system, but in Lingga village, Simpang Empat district, Karo district, although women are not considered as heirs, they get a share of the gift (pemere) as a form of respect. togirls.